Learning with Family Every Day (10) (Journal of Parents and Teachers, 2024)
The article highlights the importance of making the most of time—quality, useful, and valuable time—to do everything, to work with time, with everyone and everything. It also touches on environmental issues and includes a story about the Grandmother's Clock.
Keywords: time; make the most; clock; impotance